Legal Effectiveness and Legal Functions in Indonesia - RAHAYU, Panggih Rangga; ADIYANTO, Bama; MURTI, Jentung Wisnu; SETIYONO, Aries; KRISTHY, Mutia Evi (Indonesia Strategic Sustainability, 2024)
Purpose: This study aims to describe the Effectiveness of Law and Legal Functions in Indonesia. Law serves as justice, certainty and expediency. In the practice of law administration in Indonesia, there are times when there is a conflict between legal certainty and justice. This research will examine the effectiveness of law and legal functions in Indonesia, based on the object of research to be studied, and then this research will be based on positive law.Methodology:This research uses a descriptive qualitative approach with library research methods. Legal certainty is concrete and tangible, while justice is abstract. Therefore, in solving a legal problem, the values of justice must be prioritized.Findings: The results of this study show that the effectiveness of law enforcement in Indonesia is influenced by several factors, namely the legal factors themselves, law enforcement factors, factors of facilities or facilities that support law enforcement, and community factors.Implication:The influence of law and the concept of purpose: It can be said that the concept of influence means the attitude of action or behavior associated with the rule of law in reality, a positive effect or effectiveness that depends on the purpose or purpose of the rule of law. A legal purpose is only sometimes identically stated in a rule and is not necessarily the real reason for the rule-maker.